Bacterial nanocellulose aerogel as well as preparation method and application thereof

CN119371709AActive Publication Date: 2025-01-28SUZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411442215.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-28
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing photothermal conversion materials have low evaporation rate and poor mechanical properties, so they cannot be suitable for industrial production.

Method used

采用细菌纳米纤维素作为前驱体,通过点状扩散交联方式构筑氧化苏木精-铁络合物掺杂的细菌纳米纤维素气凝胶,并加入γ-缩水甘油醚氧丙基三甲氧基硅烷(KH560)以提高机械性能。

Benefits of technology

It significantly improves the evaporation performance and mechanical properties of gas gel, enables them to be suitable for industrialized production, and achieves about 95%of the optical conversion efficiency of about 95%during the evaporation of the solar interface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371709A_ABST
    Figure CN119371709A_ABST
Patent Text Reader

Abstract

The invention relates to bacterial nanocellulose aerogel as well as a preparation method and application thereof. The preparation method of the bacterial nanocellulose aerogel comprises the following steps: mixing bacterial cellulose, hematoxylin oxide and a silane coupling agent in deionized water for reaction to obtain a self-gel sample; ferrous sulfate is applied to the surface of the self-gel sample in a dotted diffusion mode, and after freeze drying, the bacterial nanocellulose aerogel is obtained. According to the invention, bacterial cellulose is used as a precursor, and hematoxylin-iron complex doped nanocellulose aerogel is constructed. The bacterial nanocellulose aerogel is good in photo-thermal performance, the photo-thermal conversion efficiency can reach 85% or above, meanwhile, the bacterial nanocellulose aerogel has good mechanical performance, and the bacterial nanocellulose aerogel has wide application prospects in the aspect of interface evaporator industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of interface evaporation, in particular to a bacterial nanocellulose aerogel and a preparation method and application thereof. Background Art

[0002] Aerogel is a light solid material. It forms a nano-skeleton and nano-porous network structure through the aggregation of nano-colloidal particles. It has a sponge-like microporous structure, which gives it a large specific surface area and porosity. The pores are filled with gaseous dispersion medium. It has high porosity, low density and strong adsorption performance. It is one of the lightest solid materials in the world. As traditional seawater desalination gradually fails to provide the best solution for human economy, photothermal conversion materials, as the core of seawater desalination, have excellent performance and irreplaceable significance. Therefore, researchers are gradually moving towards biomass and renewable energy.

[0003] Seawater desalination refers to the process of separating salt water from seawater by various means. At present, the mainstream seawater desalination technologies used in international commercial applications are divided into two types: thermal method and membrane method. The thermal method mainly includes low-temperature multi-effect evaporation process and multi-stage flash evaporation process, and the membrane method mainly includes reverse osmosis process. As the core part of solar desalination technology, photothermal conversion materials have been widely studied by researchers. Commonly used materials include carbon-based materials (carbon nanotubes, graphene, etc.), metal nanoparticles, conjugated polymers, semiconductor materials, etc. The Chinese patent with publication number CN116607318A discloses a preparation method and application of a photothermal conversion material. Although it has a good antibacterial effect on Escherichia coli and Staphylococcus aureus while enhancing the photothermal conversion ability, the alkali treatment, redox reaction and loaded particles in the preparation process greatly increase the production cost and the possibility of pollution; for example, the Chinese patent with publication number CN118005489A discloses a preparation method of a photothermal conversion material based on supramolecular eutectic, which optimizes the economic level of the material and reduces the cost, but the environmental requirements of its preparation process are strict and cannot simultaneously meet the requirements of low carbon, high efficiency, energy saving and environmental protection. In addition, the mechanical properties of aerogels in the prior art are poor and cannot be applied to industrial production. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the problems of low evaporation rate and poor mechanical properties of photothermal conversion materials in the prior art.

[0005] In order to solve the above technical problems, the present invention provides a bacterial nanocellulose aerogel and its preparation method and application. The bacterial nanocellulose aerogel of the present invention uses bacterial cellulose as a precursor, and constructs a bacterial nanocellulose aerogel doped with oxidized hematoxylin-iron complex by point diffusion cross-linking, which gives the aerogel good evaporation performance; at the same time, by adding γ-glycidyl ether oxypropyl trimethoxysilane (KH560), the mechanical properties of the aerogel are improved, which is convenient for industrial production. Specifically, KH560 can form a cross-linked structure with bacterial cellulose, enhance the network stability of the aerogel, thereby improving its compressive strength and toughness, and as an organic silane, the flexible chain segment in the molecule can effectively absorb external stress, improve the deformation ability of the material when it is impacted or stretched, effectively reduce the risk of interface collapse and brittle fracture, and improve the overall mechanical properties. The cross-linking of oxidized hematoxylin will form a dense and uniform cross-linked structure, so that the aerogel can better disperse and withstand pressure when under pressure, and can also limit the development and expansion of cracks, and improve the durability of the aerogel. Ferrous sulfate is mainly cross-linked with hematoxylin oxide. When ferrous sulfate is mixed with hematoxylin oxide, divalent iron ions can react with hydroxyl groups in hematoxylin oxide. In this process, divalent iron ions act as a cross-linking agent, and form a stable composite structure by coordinating with hydroxyl groups on different molecular chains to form a stable cross-linked network. The cross-linked structure increases the mutual connection points between molecules, thereby improving the overall structural stability and tensile strength of the material, and significantly improving the mechanical properties of the material. When several materials are used together, KH560 provides flexibility, while hematoxylin oxide and ferrous sulfate increase strength, and bacterial cellulose increases toughness. Under the joint action of KH560, hematoxylin oxide, ferrous sulfate and bacterial cellulose, the bacterial nanocellulose aerogel of the present invention not only has good evaporation performance, but also has strong mechanical properties.

[0006] The first object of the present invention is to provide a method for preparing bacterial nanocellulose aerogel, comprising the following steps:

[0007] S1, mixing bacterial cellulose, oxidized hematoxylin and silane coupling agent in water to obtain a self-gel sample;

[0008] S2. Applying ferrous sulfate to the surface of the self-gelling sample in a point-like diffusion manner, and obtaining the bacterial nanocellulose aerogel after freeze-drying.

[0009] Furthermore, the water in step S1 is deionized water.

[0010] Furthermore, the silane coupling agent includes γ-glycidyloxypropyltrimethoxysilane.

[0011] Further, the amount of oxidized hematoxylin added is 10%-100% of the dry weight of bacterial cellulose, such as 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, including but not limited to the above-listed values. Preferably, the value is selected from 50%, 60%, 70%, 80%.

[0012] Furthermore, the addition amount of the γ-glycidyloxypropyltrimethoxysilane is 25%-75% of the dry weight of the bacterial cellulose, such as 25%, 50%, 75%, 100%, including but not limited to the above-listed values.

[0013] Further, the amount of ferrous sulfate added is 10%-200% of the dry weight of bacterial cellulose, such as 10%, 25%, 50%, 60%, 100%, 150%, 200%, including but not limited to the above-listed values. Preferably, the value is selected from 50%, 60%, 100%, 150%.

[0014] Furthermore, the mass ratio of the hematoxylin oxide to the ferrous sulfate is (1-5):(1-4), such as 5:1, 2:1, 1:1, 1:2, 1:3, 1:4, including but not limited to the ratios listed above. Preferably, the ratio is selected from 1:1, 1:2, 1:3.

[0015] Furthermore, the small hole mesh penetration device includes a cylinder and end caps at both ends of the cylinder, the cylinder is sealed and connected to the end caps, the cylinder and the end caps are jointly enclosed to form a receiving cavity that just accommodates the self-gel sample, and the cylinder and the end caps are evenly distributed with a number of circular through holes; the aperture of the through hole is 0.430-0.755mm. Ferrous sulfate drips from the through hole, and when the ferrous sulfate contacts and reacts with the surface of the self-gel, it diffuses and cross-links around each aperture as the center, so as to form a uniform surface network cross-linking morphology, improve the uniformity and aerogel molding density. In the process of mesh diffusion from the aperture, each aperture will form an annular diffusion area extending around and inside, and at this time it will form an intersection with the diffusion circle of other apertures. If the aperture is too large, the intersection area will be too large, which may cause an increase in density; and if the aperture is too small, the intersection area will be too small, and if the intersection area is too small, the aerogel surface will be left blank, the interface reaction area of ​​the photothermal conversion will be reduced, and the efficiency will be reduced.

[0016] Furthermore, the freeze-drying temperature is -60°C to -40°C, and the freeze-drying time is 24-50 hours.

[0017] Furthermore, after ferrous sulfate is applied to the surface of the self-gelling sample in a point-diffusion manner, it needs to be left to stand for 20-40 hours to allow it to fully react.

[0018] Furthermore, in step S2, after freeze drying, solvent replacement treatment can be performed, and ethanol and tert-butanol are added to the bacterial cellulose aerogel in sequence for solvent replacement treatment, so as to remove the yellow granules precipitated by ferrous sulfate as much as possible, and at the same time increase the surface tension of bacterial nanocellulose. Tert-butanol has a greater surface tension than ethanol, and the hydrophilicity of the prepared aerogel is enhanced during the solvent replacement process. Moreover, ethanol and tert-butanol are volatile substances and do not require subsequent treatment.

[0019] The second object of the present invention is to provide a bacterial nanocellulose aerogel prepared by the above preparation method.

[0020] The third object of the present invention is to provide an application of the above-mentioned bacterial nanocellulose aerogel in the preparation of an interfacial evaporator.

[0021] Beneficial effects of the present invention:

[0022] 1. The present invention uses bacterial cellulose as a precursor to construct a nanocellulose aerogel doped with oxidized hematoxylin-iron complex. The oxidized hematoxylin and iron ions form a complex that makes the aerogel black, thereby improving the light absorption efficiency of the aerogel. At the same time, ferrous sulfate is cross-linked by point diffusion, so that ferrous sulfate is diffused point-wise on the surface of the self-gel sample through a small hole mesh penetration device. The point diffusion cross-linking can make ferrous sulfate diffuse evenly on the surface of the self-gel sample. While each point diffuses to the surrounding, it also diffuses inward at basically equal distances, so that there are enough gaps inside the aerogel to improve the thermal insulation performance and further improve the evaporation efficiency. The bacterial nanocellulose aerogel thus obtained has an extremely high porosity and an extremely low density, which is conducive to the thermal diffusion phenomenon of water molecules during interfacial evaporation. In addition, under the joint action of bacterial cellulose, oxidized hematoxylin, ferrous sulfate and KH560, the aerogel presents a dense three-dimensional structure, and the fibers are cross-linked with each other, which also improves the mechanical properties of the aerogel.

[0023] 2. The preparation method of the present invention has the characteristics of simple process flow, green sustainability, high efficiency, low cost, etc., and is suitable for industrial production. Moreover, the bacterial nanocellulose aerogel obtained by the preparation method provided by the present invention has a porosity of more than 99% and a density of less than 0.01g / cm 3 , which is beneficial to the thermal diffusion of water molecules during the interface evaporation process. Therefore, the photothermal conversion efficiency of the bacterial nanocellulose aerogel provided by the present invention during the solar interface evaporation process can reach about 95%. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein

[0025] Figure 1 is a process flow chart of the bacterial nanocellulose aerogel of the present invention;

[0026] Figure 2 It is a schematic diagram of the process of using the bacterial nanocellulose aerogel of the present invention in preparing an interfacial evaporator;

[0027] Figure 3 This is a schematic diagram of the structure of the quantitative mold used in the present invention;

[0028] Figure 4 It is a schematic diagram of the structure of the small hole mesh point penetration device used in the present invention;

[0029] Figure 5 This is a process diagram of the present invention using a small hole mesh point penetration device to perform point diffusion cross-linking;

[0030] Figure 6 1 is a compressive stress-strain curve analysis diagram of Example 1 and Comparative Example 1 of the present invention, wherein A is the compressive stress-strain curve of Comparative Example 1, and B is the compressive stress-strain curve of Example 1;

[0031] Figure 7 is the XRD spectrum under different ferrous sulfate contents;

[0032] Figure 8 These are sample diagrams of Example 1 and Comparative Examples 3-6 of the present invention, wherein a: sample diagram of Comparative Example 3; b: sample diagram of Comparative Example 4; c: sample diagram of Comparative Example 5; d: sample diagram of Comparative Example 6; e: sample diagram of Example 1;

[0033] Fig. 9 These are SEM images of Example 1 of the present invention and Comparative Examples 3-6, wherein (a1) and (a2): SEM image of Comparative Example 3; (b1) and (b2): SEM image of Comparative Example 4; (c1) and (c2): SEM image of Comparative Example 5; (d1) and (d2): SEM image of Comparative Example 6; (e1) and (e2): SEM image of Example 1. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0035] The small hole mesh point penetration device 2 used in the present invention is as follows Figure 4As shown, the small hole mesh penetration device 2 includes a cylinder 21 and end caps 23 located at both ends of the cylinder 21, the cylinder 21 and the end caps 23 are sealed, and the cylinder 21 and the end caps 23 are jointly surrounded to form a receiving cavity 20 that just accommodates the self-gel sample, and a plurality of circular through holes 22 are evenly distributed on the cylinder 21 and the end caps 23, and the aperture of the through holes is 0.430-0.755mm. When in use, the self-gel sample is placed in the receiving cavity 20, and ferrous sulfate solution is dripped onto the outside of the cylinder 21 and the end caps 23, and the ferrous sulfate solution is dripped onto the surface of the self-gel sample through the through holes 22, thereby realizing the point-like diffusion cross-linking of ferrous sulfate in the self-gel sample.

[0036] In order to better accommodate the self-gel sample in the accommodating cavity 20 and to allow the ferrous sulfate dripped from the through hole 22 to better contact the self-gel sample, the present invention further provides a quantitative mold 1, which is adapted to the small hole mesh infiltration device 2, so that the self-gel sample separated from the quantitative mold 1 can be just accommodated in the accommodating cavity 20 of the small hole mesh infiltration device 2 and fit with the inner wall of the cylinder 21.

[0037] Preferably, the quantitative mold 1 can also be nested just outside the small hole mesh penetration device 2 in the present invention. When the quantitative mold 1 is nested outside the small hole mesh penetration device 2, the bacterial cellulose, oxidized hematoxylin, silane coupling agent and deionized water are directly self-gelled in the small hole mesh penetration device 2. Since the quantitative mold 1 is nested just outside the small hole mesh penetration device 2, the self-gelled sample will not leak from the through hole 22 of the small hole mesh penetration device 2. After the self-gelation is completed, the quantitative mold 1 is removed, and then the point diffusion cross-linking is performed.

[0038] Example 1: Effects of different amounts of ferrous sulfate solution on aerogel

[0039] (1) A bacterial cellulose aqueous dispersion with a mass fraction of 0.8 wt% was mixed with water and magnetically stirred at room temperature for ≥ 30 min to obtain a bacterial cellulose (BC) aqueous dispersion with a mass fraction of 0.4 wt%.

[0040] (2) 50% of the dry weight of bacterial cellulose was added with hematoxylin (OH) oxide and 50% of the dry weight of bacterial cellulose was added with γ-glycidyloxypropyltrimethoxysilane (KH560) and stirred for ≥10 min respectively. Then, the mixture was injected into a 5 mL quantitative mold 1 and allowed to self-gel for 12 hours.

[0041] (3) Dissolving different masses of ferrous sulfate in deionized water to prepare ferrous sulfate solutions with different contents, and placing the self-gel samples in a small hole mesh penetration device 2 to penetrate the surface of the self-gel in the form of droplets and leaving the gel to stand for 24 hours to allow it to react fully on the surface; placing the sample in a refrigerator for 24 hours to obtain a black solid sample; wherein the mass of ferrous sulfate accounts for 10%, 25%, 50%, 100%, 150%, and 200% of the dry weight of the bacterial cellulose, respectively.

[0042] (4) The black solid sample was freeze-dried for 48 h to obtain bacterial nanocellulose aerogel doped with oxidized hematoxylin-iron complex.

[0043] (5) An X-ray diffractometer was used to characterize the changes in the aggregation structure of the aerogel. At the same time, the sample was placed under a xenon arc light source, and its initial mass was weighed. The sample mass was recorded every 5 minutes (a total of 1 hour) to evaluate the light evaporation capacity v1 of each group of samples and the dark evaporation capacity v2 of each group of samples in the same environment for 1 hour to evaluate the evaporation capacity of bacterial nanocellulose aerogel to simulated seawater. An infrared thermal imager was used to observe the surface temperature changes of the aerogel, and the initial temperature T1 and stable temperature T2 during the test were recorded. The results are as follows: Figure 7 , as shown in Table 1. The analysis results show that, except for the aerogel with 200% ferrous sulfate content, the others have obvious (101), (101-), (002) and (040) crystal planes, showing the characteristics of type I cellulose. With the increase of ferrous sulfate content, the characteristic peak of cellulose weakened, and new peaks appeared near 19.9°, 24.8°, 27.3° and 28.6°, which belonged to ferrous sulfate and its complex with oxidized hematoxylin. After the photothermal conversion of each group of aerogels, the average surface temperature rise was about 26.4°C, and the stable temperature T2 value remained between 45°C and 47°C. With the increase of ferrous sulfate concentration, the η values ​​of each group of aerogel samples were 65.1%, 66.5%, 80.5%, 75.8%, 73.6%, and 71.0%, respectively. Like the v1 value, the peak value appeared when the ferrous sulfate content was 50%, and the η value could reach about 74% or more when the ferrous sulfate content was between 50% and 150%. The calculation process of evaporation rate is as follows:

[0044] Water evaporation rate and photothermal conversion efficiency are two key indicators for measuring solar water evaporation performance. Water evaporation refers to the amount of water evaporated per unit area and per unit time, and the unit is kg m -2 h -1 It can be calculated by formula 1-1:

[0045]

[0046] Among them, Δm (kg) represents the mass of evaporated water; s (m2 ) represents the evaporation area of ​​aerogel; Δt(h) represents the evaporation time.

[0047] Photothermal conversion efficiency is an important indicator to measure the ability of photothermal materials to convert light energy into thermal energy, which can be calculated by formula 1-2:

[0048]

[0049] Q=c(T1-To)(1-4)

[0050] Where m is the evaporation rate under solar radiation minus the evaporation rate under dark conditions, in kg m- 2 h- 1 ;H LV is the latent heat required to evaporate water, in J kg- 1 ; T1 is the stable temperature of the evaporation surface; T0 is the initial temperature of the evaporation surface; Q is the heat required to increase the water temperature, in J kg- 1 ; c is the specific heat capacity of water, unit is 4.2J g- 1 K- 1 ; Ein is the energy input of the incident light, in kW m- 2 .

[0051] Under the same conditions, during the evaporation efficiency measurement of the same group of experiments, the porosity of the aerogel reached more than 99%. The difference in temperature and humidity will cause a certain impact on the aerogel's heating speed and moisture absorption rate, which may cause a certain difference in the light evaporation rate and dark evaporation rate measured in different time periods, but the final result will not have too much impact, and the result will remain at an error value of about ±3.5%.

[0052] Table 1 Effect of the amount of ferrous sulfate added on the evaporation performance of aerogel

[0053]

[0054] Example 2: Effect of the amount of oxidized hematoxylin added on the evaporation effect of aerogel

[0055] (1) mixing a bacterial cellulose aqueous dispersion having a mass fraction of 0.8 wt % with water, and magnetically stirring at room temperature for ≥ 30 min to obtain a bacterial cellulose aqueous dispersion having a mass fraction of 0.4 wt %;

[0056] (2) Add different amounts of oxidized hematoxylin, then add KH560 accounting for 50% of the dry weight of bacterial cellulose and stir evenly for ≥10 min, then inject into a 5 mL quantitative mold 1 for self-gelation for 12 hours. The amount of oxidized hematoxylin added is 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100% of the dry weight of bacterial cellulose.

[0057] (3) Since it was proved in implementation 1 that the evaporation rate effect is optimal when the mass ratio of hematoxylin oxide to ferrous sulfate is 1:1, a ferrous sulfate solution is prepared according to the hematoxylin oxide content in step (2) at a mass ratio of 1:1, and the self-gel samples are placed in a small hole mesh penetration device 2 respectively, and the self-gel surface is fully penetrated in the form of droplets and the gel is left to stand for 24 hours to allow it to react fully on the surface; it is placed in a refrigerator for 24 hours to obtain a black solid sample.

[0058] (4) The black solid sample was freeze-dried for 48 h to obtain bacterial nanocellulose aerogel doped with oxidized hematoxylin-iron complex.

[0059] (5) The samples were placed under a xenon arc light source, and their initial mass was weighed. The sample mass was recorded every 5 minutes (1 hour in total) to evaluate the light evaporation capacity v1 of each group of samples, and the dark evaporation capacity v2 of each group of samples in the same environment for 1 hour was recorded to evaluate the evaporation capacity of the aerogel for simulated seawater. The surface temperature change of the aerogel was observed using an infrared thermal imager, and the initial temperature T1 and stable temperature T2 during the test were recorded. The results are shown in Table 2. The analysis results show that the η value of each group of aerogels shows a certain trend of first increasing and then decreasing. When the content is low, that is, when the oxidized hematoxylin (OH) accounts for 10%-40% of the dry weight of bacterial cellulose (BC), the evaporation efficiency is basically maintained at a low level of 70%, and when the OH content is between 50% and 90%, the evaporation efficiency shows a significant trend of first increasing and then decreasing, and the optimal value is 95.4%. That is, when the OH content accounts for 60% of the dry weight of BC, the η value reaches the best value of 95.4%. It can also be observed from the table that it is higher when the OH content reaches 100%, and the η value increases again from 71.8% when the OH content is 90% to 76.1%. It is speculated that the oxidized hematoxylin may undergo a qualitative change at a higher content, thereby affecting the final performance of the photothermal material and increasing its efficiency instead.

[0060] Table 2 Effect of different addition amounts of oxidized hematoxylin on the evaporation performance of aerogel

[0061]

[0062] (6) The aerogel prepared by adding 60% of the above-mentioned oxidized hematoxylin was subjected to solvent replacement treatment. After the aerogel was freeze-dried, ethanol and tert-butanol were added to the bacterial cellulose aerogel in sequence for solvent replacement treatment, thereby obtaining the bacterial cellulose aerogel after solvent replacement.

[0063] Example 3

[0064] (1) A bacterial cellulose aqueous dispersion having a mass fraction of 0.8 wt % is mixed with water and magnetically stirred at room temperature for ≥ 30 min to obtain a bacterial cellulose aqueous dispersion having a mass fraction of 0.4 wt %.

[0065] (2) First, add 60% of the dry weight of bacterial cellulose in the amount of oxidized hematoxylin, then add different amounts of KH560 and stir evenly for ≥10 min, then inject into a 5 mL quantitative mold 1 and allow to gel for 12 hours. The amount of KH560 added is 25%, 50%, 75%, and 100% of the dry weight of bacterial cellulose.

[0066] (3) A ferrous sulfate solution containing 60% of the dry weight of bacterial cellulose is prepared, and the self-gel sample is placed in a small-pore mesh penetration device 2 to penetrate the surface of the self-gel in the form of droplets, and the gel is allowed to stand for 24 hours to allow it to react fully on the surface; and the sample is placed in a refrigerator for 24 hours to obtain a black solid sample.

[0067] (4) The black solid sample was freeze-dried for 48 h to obtain bacterial nanocellulose aerogel doped with oxidized hematoxylin-iron complex.

[0068] (5) The aerogel was placed under a xenon arc light source, and its initial mass was weighed. The sample mass was recorded every 5 minutes (a total of 1 hour), and the light evaporation capacity v1 of each group of samples was evaluated. The dark evaporation capacity v2 of each group of samples in the same environment for 1 hour was recorded to evaluate the evaporation capacity of the aerogel for simulated seawater. The surface temperature change of the aerogel was observed by an infrared thermal imager, and the initial temperature T1 and the stable temperature T2 during the test were recorded. The results are shown in Table 3. The analysis results show that with the increase of KH560 content, the η value results reached 88.3%, 94.1%, 86.5%, and 84.7%, respectively, and remained above about 85%. In particular, the 50% KH560 sample group achieved better results. The improvement of mechanical properties can enhance the strength and hardness of aerogel materials, making them more wear-resistant, pressure-resistant and tensile-resistant, thereby improving their service life and stability. Secondly, the impact resistance of aerogel materials can also be increased, so that they are not easily damaged or deformed when subjected to external impact or extrusion. In addition, the processing performance of aerogel materials can be improved, making them easier to carry out processing operations such as molding, cutting and assembly. Different from the sample without KH560, η is relatively weakened as the KH560 content increases, but η reaches the optimal value of 94.1% when the content accounts for 50% of the BC dry weight. Therefore, it is speculated that the increase of KH560 may weaken the photothermal conversion ability of the aerogel. However, considering the insufficient strength and water resistance of the aerogel when no KH560 is added or its content is low, and the high concentration causes the evaporation efficiency to be weakened, the intermediate value is still preferred: adding 50% KH560.

[0069] Table 3 Effect of different addition amounts of KH560 on the evaporation performance of aerogel

[0070]

[0071] Comparative Example 1

[0072] (1) A bacterial cellulose aqueous dispersion having a mass fraction of 0.8 wt % is mixed with water and magnetically stirred at room temperature for ≥ 30 min to obtain a bacterial cellulose aqueous dispersion having a mass fraction of 0.4 wt %.

[0073] (2) Add oxidized hematoxylin accounting for 50% of the dry weight of bacterial cellulose and stir evenly for ≥10 min, then inject it into a 5 mL quantitative mold 1 for self-gelation for 12 hours.

[0074] (3) Prepare ferrous sulfate with a content of 50% of the dry weight of bacterial cellulose, put the self-gel sample into a small-pore mesh penetration device 2, and let it penetrate the surface of the self-gel in the form of droplets, and let the gel stand for 24 hours to allow it to react fully on the surface; put it in a refrigerator and freeze it for 24 hours to obtain a black solid sample.

[0075] (4) The black solid sample was freeze-dried for 48 h to obtain bacterial nanocellulose aerogel doped with oxidized hematoxylin-iron complex.

[0076] (5) The aerogel prepared in Example 1 with a mass of ferrous sulfate being 50% of the dry weight of bacterial cellulose was selected for testing. The obtained aerogel was tested for the cyclic compression stress-strain curve of the columnar aerogel sample using a universal strength machine equipped with a 500N sensor. The sample diameter and height were accurately measured with a vernier caliper before the test. The compression and return rates were set to 5 mm / min, and the maximum compression strain was 80%. Finally, the compression modulus and elastic recovery rate were calculated based on the test results. The mechanical properties results are shown in Figure 6 (A is the compressive stress-strain curve of comparative example 1, and B is the compressive stress-strain curve of embodiment 1). Figure 6 Analysis shows that: with the addition of KH560, the elastic recovery rate of the sample increased from 39.68% to 53.39%, indicating that KH560 has a certain cross-linking and strengthening effect on the aerogel material itself, that is, KH560 improves the mechanical properties of the material without affecting the hydrophilicity of the sample itself. The above data show that the addition of KH560 promotes the enhancement of the strength of the three-dimensional structure of the aerogel.

[0077] Comparative Example 2

[0078] (1) A bacterial cellulose aqueous dispersion having a mass fraction of 0.8 wt % is mixed with water and magnetically stirred at room temperature for ≥ 30 min to obtain a bacterial cellulose aqueous dispersion having a mass fraction of 0.4 wt %.

[0079] (2) Add oxidized hematoxylin accounting for 50% of the dry weight of bacterial cellulose and stir evenly for ≥10 min, then inject it into a 5 mL quantitative mold 1 for self-gelation for 12 hours.

[0080] (3) preparing ferrous sulfate with a content of 50% of the dry weight of bacterial cellulose, placing the self-gelling sample into device 2, and pouring the prepared ferrous sulfate solution into device 2, so that the self-gelling sample is immersed in the ferrous sulfate solution; placing the self-gelling sample in a refrigerator and freezing it for 24 hours to obtain a black solid sample.

[0081] (4) The black solid sample was freeze-dried for 48 hours to obtain black nanocellulose aerogel doped with oxidized hematoxylin-iron complex.

[0082] (5) The aerogel prepared in Example 1 with the mass of ferrous sulfate being 50% of the dry weight of bacterial cellulose was selected for testing. The samples of Example 1 and Comparative Example 2 were placed under a xenon arc light source, and their initial masses were weighed while recording the mass of the samples every 5 minutes (a total of 1 hour). The light evaporation capacity v1 of each group of samples was evaluated, and the dark evaporation capacity v2 of each group of samples in the same environment for 1 hour was recorded to evaluate the evaporation capacity of the black aerogel for simulated seawater. The surface temperature change of the aerogel was observed using an infrared thermal imager, and the initial temperature T1 and the stable temperature T2 during the test were recorded. The results are shown in Table 4. In the same environment, the aerogel formed by point diffusion can achieve a high efficiency of 97.5% in the process of photothermal conversion. Compared with the sample of Comparative Example 2 formed by the immersion method, the efficiency is increased by 11.7%, and the light evaporation efficiency is effectively improved. Through the surface point diffusion cross-linking, the sulfated liquid iron can be evenly diffused on the surface of the autogel, and each point diffuses to the surrounding while diffusing inward at basically equal distances. Due to its own weight, it will diffuse inward with a certain gradient from bottom to top, and then there will be enough gaps inside to provide effective thermal insulation performance to increase the thermal stability temperature of the photoreaction rate, thereby improving the evaporation efficiency, and obtaining bacterial nanocellulose aerogels with extremely high porosity and extremely low density, which is conducive to the thermal diffusion phenomenon of water molecules during the interface evaporation process. The obtained bacterial nanocellulose aerogel has a high light-to-heat conversion efficiency while ensuring good mechanical properties. The preparation method of bacterial nanocellulose aerogel provided by the present invention has the characteristics of green sustainability, high efficiency, low cost, etc., and is suitable for industrial production.

[0083] Table 4 Effect of cross-linking method on the evaporation performance of aerogel

[0084]

[0085] Comparative Example 3

[0086] Take a bacterial cellulose aqueous dispersion with a mass fraction of 0.8wt% and mix it with water, and stir it magnetically for ≥30min at room temperature to obtain a bacterial cellulose aqueous dispersion with a mass fraction of 0.4wt%. Inject it into a 5mL quantitative mold 1 and let it gel for 12 hours. Then put it in a refrigerator and freeze it for 24 hours to obtain a solid sample. The solid sample is freeze-dried for 48 hours to obtain a bacterial nanocellulose aerogel.

[0087] Comparative Example 4

[0088] Take a bacterial cellulose aqueous dispersion with a mass fraction of 0.8wt% and mix it with water, and stir it magnetically for ≥30min at room temperature to obtain a bacterial cellulose aqueous dispersion with a mass fraction of 0.4wt%. Add KH560 accounting for 50% of the dry bacterial cellulose and stir it evenly for ≥10min, then inject it into a 5mL quantitative mold 1 for self-gelation for 12 hours. Then put it in a refrigerator and freeze it for 24h to obtain a solid sample. The solid sample is freeze-dried for 48 hours to obtain bacterial nanocellulose aerogel.

[0089] Comparative Example 5

[0090] Take a bacterial cellulose aqueous dispersion with a mass fraction of 0.8wt% and mix it with water, and stir it magnetically for ≥30min at room temperature to obtain a bacterial cellulose aqueous dispersion with a mass fraction of 0.4wt%. Add 60% of the dry weight of bacterial cellulose oxidized hematoxylin and stir it evenly for ≥10min, then inject it into a 5mL quantitative mold 1 for self-gelation for 12 hours. Then put it in a refrigerator and freeze it for 24h to obtain a solid sample. The solid sample is freeze-dried for 48 hours to obtain bacterial nanocellulose aerogel.

[0091] Comparative Example 6

[0092] Take a bacterial cellulose aqueous dispersion with a mass fraction of 0.8wt% and mix it with water, and stir it magnetically for ≥30min at room temperature to obtain a bacterial cellulose aqueous dispersion with a mass fraction of 0.4wt%. Prepare a ferrous sulfate solution with a content of 60% of the dry weight of bacterial cellulose, put its self-gel sample into a small hole mesh penetration device 2 in the form of droplets to fully penetrate the surface of the self-gel body and let the gel stand for 24 hours to allow it to react fully on the surface; put it in a refrigerator and freeze it for 24 hours to obtain a solid sample. The solid sample is freeze-dried for 48 hours to obtain a nanocellulose aerogel.

[0093] The aerogel prepared in Example 1 in which the mass of ferrous sulfate was 50% of the dry weight of bacterial cellulose was selected for testing, and digital photos were obtained by taking pictures of Comparative Examples 3-6 and Example 1 at the same angle. Figure 8 The surface morphology of the aerogel was characterized by scanning electron microscopy, and the results were shown in Figure 2. Fig. 9; The analysis results show that the PBC aerogel in (a) is white. Since KH560 is a colorless and transparent substance, the color of the BC-560 aerogel in (b) does not change after it is added, but its three-dimensional framework is improved, making its appearance more three-dimensional and improving the local collapse phenomenon; Oxidized hematoxylin is yellowish brown, so after adding it on the basis of PBC, it is observed that its color in (c) does not undergo a significant mutation. Similar to the addition of KH560, its mechanical properties are increased, and its surface collapse is improved, which may be due to the cross-linking that occurs during the addition process; Ferrous sulfate (FE) itself is green but is easily oxidized to trivalent iron and becomes yellow. Therefore, it can be clearly observed in (d) that the BC-FE aerogel is yellow after oxidation, but there are obvious concave lines on its surface, and the pores The size difference is obvious, and it is speculated that the amount of KH560 has a great influence on the appearance of the aerogel. The BC-OH-FE-560 aerogel prepared by the optimal process formula in (e) is black. Through the comparison of samples, it can be inferred that the main reason is that the complex obtained by the chemical reaction of oxidized hematoxylin and iron ions affects the color of the final product, and BC-OH-FE-560 presents a relatively flat appearance, but the compactness is increased. As shown in the SEM image (a2), at low magnification, the aerogel prepared by PBC exhibits an obvious lamellar cavity structure. This large cavity is caused by the growth of large ice crystals during the freezing process. With the addition of KH560, as shown in Figure (b2), its surface smoothness is improved, and the framework develops from a two-dimensional layered structure to a three-dimensional framework, making its structure more three-dimensional. (a1) and (b1) show the microscopic morphology of the aerogel cavity wall at high magnification. In PBC, bacterial cellulose fibers are interspersed and stacked to form a relatively dense lamellar structure. With the addition of KH560, the "sharpness" of the edge of the aerogel cavity wall is reduced, the boundary between the fibers is gradually blurred, and the edge of the cavity wall gradually becomes thicker; as shown in (c1) and (c2), compared with PBC, with the addition of oxidized hematoxylin, the lamellar morphology of the original sample microstructure becomes larger, and the boundary between the fibers is clear, the three-dimensional cavity structure is obvious, the cavity wall at high magnification has a bending tendency, and nodes appear on its surface; and in Figures (d1) and (d2), the "bundle-like" texture on its surface can be clearly observed. It is speculated that the appearance of this appearance is related to the formation of self-gel by ferrous sulfate impregnation, and this texture is formed by bundling. In addition, the addition of ferrous sulfate blurs the boundary between the fibers, which increases the surface smoothness.In the optimal sample image at high magnification shown in (e1), obvious cross-linking nodes can be observed, but in addition to the nodes, the connection of fibers at various locations can be clearly observed. The dense cross-linking degree of the fibers is speculated to increase the structural bearing capacity and make it dense and three-dimensional, and the cavity is more three-dimensional at low magnification. Compared with PBC, the distance between the layered structures has increased. Therefore, it is speculated that within a certain range, the pore volume of the aerogel has increased, which also increases the amount of static air contained in the aerogel, thereby increasing its thermal insulation performance. In the process of contact with the liquid, the photothermal conversion of bacterial nanocellulose aerogel can better maintain the continuous rise of water temperature under the interface evaporation mode, and effectively improve the photothermal conversion efficiency.

[0094] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing bacterial nanocellulose aerogel, characterized in that: The following steps are involved: S1, mixing bacterial cellulose, oxidized hematoxylin and silane coupling agent in water to obtain a self-gel sample; S2. Applying ferrous sulfate to the surface of the self-gelling sample in a point-like diffusion manner, and obtaining the bacterial nanocellulose aerogel after freeze-drying.

2. The preparation method according to claim 1, characterized in that: The silane coupling agent includes γ-glycidyloxypropyltrimethoxysilane.

3. The preparation method according to claim 1, characterized in that: The added amount of the oxidized hematoxylin is 10%-100% of the dry weight of the bacterial cellulose.

4. The preparation method according to claim 1, characterized in that: The added amount of the silane coupling agent is 25%-75% of the dry weight of the bacterial cellulose.

5. The preparation method according to claim 1, characterized in that: The added amount of ferrous sulfate is 10%-200% of the dry weight of bacterial cellulose.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the hematoxylin oxide to the ferrous sulfate is (1-5): (1-4).

7. The preparation method according to claim 1, characterized in that: The point diffusion method is achieved by a small hole mesh penetration device; The small hole mesh point permeation device comprises a cylinder and end caps at both ends of the cylinder, the cylinder and the end caps are sealed and connected to form a receiving cavity that just accommodates the self-gelling sample, and a plurality of circular through holes are evenly distributed on the cylinder and the end caps; The through hole has a diameter of 0.430-0.755 mm.

8. The preparation method according to claim 1, characterized in that: The freeze-drying temperature is -60°C to -40°C, and the freeze-drying time is 24-50 hours.

9. A bacterial nanocellulose aerogel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the bacterial nanocellulose aerogel according to claim 9 in preparing an interfacial evaporator.

Citation Information

Patent Citations

  • Photothermal conversion material and preparation method and application thereof

    CN116607318A

  • Preparation method of photo-thermal conversion material based on supramolecular eutectic

    CN118005489A

  • Photo-thermal conversion material with nano heterostructure as well as preparation method and application thereof

    CN113372620A

  • Polydopamine / ferrous sulfide composite photo-thermal antibacterial material as well as preparation method and application thereof

    CN115381963A

  • Bacterial nanocellulose transparent film, manufacturing method thereof, and packaging material using the same

    US20230110936A1